Cross sectional study of prevalence of LPRD at tertiary care hospital - Gaur, Raghvendra Singh; Patra, Paromita (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Reflux means return or regurgitation of fluid. When symptoms arise due to reflux of stomach contents into the pharynx and larynx it is termed as laryngopharyngeal reflux disease (LPRD). GERD and LPRD are two different entities and the management principle of GERD doesn’t apply to LPRD. We designed a cross sectional study to evaluate the prevalence of laryngopharyngeal reflux among the patients visiting the ENT outpatient department over a duration of one year. Methods: Patients presenting with throat and voice symptoms for more than a month were included in the study. The reflux symptom index (RSI) put forward by Belafsky et al was used to assess the symptoms of reflux. A diagnosis of reflux was made if the patient had an RSI score >13. Results: A total of 2669 patients included in study period, out of which 1316 (49.3%) were males and 1353 (50.7%) were females. Out of the 2669, 1938 (72.6%) patients were found to have a RSI of >13. Out of the 1938 patients subjected to 70 laryngoscopy 1842 patients (95%) were found to have a RFS >7. Of the 1842 patients with RFS >7, 1234 were males (67%) and 608 were females (33%). Conclusions: In a developing country like India, where resources and man power are limited, symptoms of laryngopharyngeal reflux might often be overlooked. The diagnosis and treatment protocol for LPRD needs to be standardized through more long term studies in the manner it has been done for GERD.